Analysis of the response of non-steroidal anti-inflammatory drugs in bone repair in patients submitted to osteogenic distraction - Teixeira, Dayane da Silva Cardozo; Barros, Fernando Vieira de; Rodrigues, Cássio Vinícius Navas; Rivero, Angel Antonio Morillo; Ferreira, Emilene Dias Fiuza (Seven Editora, 2024)
Distraction osteogenesis is a systemic procedure that can be performed using an external fixator to promote bone defense and repair in different conditions, such as severe trauma and correction of deformities. The bone healing process involves phases of inflammation, which are necessary for healing. Traumatic injuries trigger the production of cytokines that stimulate the release of prostaglandins, which helps in this healing process. This study aimed to analyze the evolution of patients who were admitted to osteogenic distraction without the use of non-steroidal anti-inflammatory drugs (NSAIDs) and to present studies that address the relationship between the use of these drugs and the delay in bone healing. NSAIDs act by inhibiting isoenzymescyclooxygenases (COX) 1 and 2 and their action on COX 2 leads to a decrease in prostaglandins, quenches the inflammatory process, which consequently interferes with the osteogenesis switch and fracture healing. A prospective randomized study reported that the use of NSAIDs in patients admitted to total arthroplasty after hip fractures evolved in more fractures and complications, demonstrating the possible transition of these medications in bone healing. In this study, osteogenic distraction without the use of non-steroidal anti-inflammatory drugs (NSAIDs) showed good results in bone repair in patients with severe fractures. Patients demonstrated that this treatment provided an efficient process of bone healing and neoformation, which resulted in a shorter duration of the distraction process. It is concluded that the interference of these drugs in the inflammatory response can impair bone healing. DOI:https://doi.org/10.56238/sevened2023.007-048